MEASURING PEDESTRIAN CATCHMENT AREA AROUND THE CAMPUS AS DEVELOPMENT CORE IN THE SUBURBS OF INDONESIA. CASE STUDY OF YOGYAKARTA’S SUBURBAN PUBLIC UNIVERSITY - Muhammad Ikram Ulman Idris; Takeru Sakai; Prasanna Divigalpitiya (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2020)
Indonesia is facing a rapid population growth in urban areas, thus affecting massive expansion throughout city center. Indonesia’s way of urban development dominated by low density of land use. To pursue the successive case of developed countries that concentrating the development around the transit nodes to countermeasure the urban sprawl, we collected some suburban state universities in Indonesia and observed the possibility for higher education services to stimulate the compact growth around the campus. This research found that walkable area around campus has a different characteristic and revealed that the catchment areas are strongly depends on number of campus size and gates. In conclusion, campus has an important role to provide a walkable area around its location, and will need to be considered in the future studies and decision making steps by Indonesian city authorities.